2011
DOI: 10.1021/jp203292h
|View full text |Cite
|
Sign up to set email alerts
|

Methionine Ligand Lability in Bacterial Monoheme Cytochromes c: An Electrochemical Study

Abstract: The direct electrochemical analysis of adsorbed redox active proteins has proven to be a powerful technique in biophysical chemistry, frequently making use of the electrode material pyrolytic “edge-plane” graphite. However many heme-bearing proteins such as cytochromes c have been also examined systematically at alkanethiol-modified gold surfaces, and previously we have reported the characterization of the redox properties of a series of bacterial cytochromes c in a side-by-side comparison of carbon and gold e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 83 publications
(259 reference statements)
4
24
0
Order By: Relevance
“…1 Here, we have extended these findings, by both interrogating the nature of the Met-loss state and demonstrating the generality of the conformational change (and the energetics thereof) as monoheme cyts c interact with EPG electrodes.…”
Section: ■ Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…1 Here, we have extended these findings, by both interrogating the nature of the Met-loss state and demonstrating the generality of the conformational change (and the energetics thereof) as monoheme cyts c interact with EPG electrodes.…”
Section: ■ Discussionsupporting
confidence: 53%
“…1 We concluded that interaction with the EPG surface substantially lowers the free energy for the conformational rearrangement of the Met-donating loop for the Ht cytochrome. 1 Here, we build upon our previous findings of Met-loss behavior by extending our characterization of bacterial monoheme cytochromes c, and we demonstrate that the phenomenon is general to Met-/Hisligated cytochromes c. We show that the relative propensity for loss of the Met-ligand can be directly correlated to the global thermal stability of the cyt c of interest, though not the apparent stability of the Fe−Met bond alone. Finally, we find that the pK a values for the Fe (II/III) redox couple for the various Met-loss states are all largely similar, showing a distinct pattern of H + -coupling that evokes other precedents of bis-His-ligated cyts c, yet may not unambiguously implicate a specific misligated state.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Instead, the unfolded state of these proteins is characterized by only a low potential signal, which, in some proteins was similar to the folded Met‐loss form while differing in others depending on the protein source. The Met61Ala mutant in Hydrogenobacter thermophilus (Ht) cyt c , expected to produce a His/aqua coordination environment without the axial Met ligand, showed a single low potential peak at −163 mV, which increased to −69 mV in the imidazole‐bound form, where the external imidazole was expected to occupy the 6th coordination position of the heme …”
Section: Resultsmentioning
confidence: 99%
“…The four hemes have two histidine as an axial ligand, so that redox potential of the hemes is low compared with Met-Fe-His heme, such as cytochrome c. 15 Thus, cytochrome c 3 has multiple redox states caused by four hemes redox, and the electron pool effect works during the four hemes redox.…”
mentioning
confidence: 99%